2021
DOI: 10.1016/j.immuni.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus and cynomolgus macaque immunoglobulin heavy-chain genotyping yields comprehensive databases of germline VDJ alleles

Abstract: Highlights d Macaque germline gene inference identifies several hundred novel IGV alleles d Rhesus and cynomolgus macaques display overlapping IGV allelic content d Analysis of macaque IGV germline genes suggests frequent structural variation d Comprehensive IG databases are essential for analysis of somatic hypermutation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(117 citation statements)
references
References 45 publications
4
113
0
Order By: Relevance
“…D20-isolated mAbs are clonally related and use the VH4.11_S9546, JH 5–1*01_S8786, lib4kappa_12 and JK2*01 or JK4*01 germline genes [ 26 ] ( Fig 1E ). The somatic hyper mutation (SHM) levels in VH and VL range from 4.2–17.5% and 3.1–11.1% at the residue (aa) level, respectively ( Fig 1E ) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…D20-isolated mAbs are clonally related and use the VH4.11_S9546, JH 5–1*01_S8786, lib4kappa_12 and JK2*01 or JK4*01 germline genes [ 26 ] ( Fig 1E ). The somatic hyper mutation (SHM) levels in VH and VL range from 4.2–17.5% and 3.1–11.1% at the residue (aa) level, respectively ( Fig 1E ) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that the Ig loci of natural outbred organisms are known to be extremely diverse, much of our understanding of the mechanisms dictating V(D)J recombination have come from studies of inbred models. However, even in inbred models, it has been demonstrated that Ig genetic diversity is more extensive than initially appreciated, in many cases mirroring (or even exceeding) what has been observed in human populations and other more outbred organisms (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In mouse, for example, a comparison of germline V H sequences between C57BL/6 and BALB/c revealed surprisingly little overlap in the germline repertoires of these two strains.…”
Section: The V H Gene Usage Conundrummentioning
confidence: 98%
“…We used single memory B cell sorting to isolate mAbs from animals that showed the highest serum [26] (Fig 1E). The somatic hyper mutation (SHM) levels in VH and VL range from 4.2-16.7% and 3.1-11.1% at the residue (aa) level, respectively (Fig 1E) [27].…”
Section: Fig)mentioning
confidence: 99%